Malaysian new ICT policy : regulatory reform and the new mode of governance / Ahmad Naqiyuddin Bakar - Bakar, Ahmad Naqiyuddin (Universiti Teknologi MARA, Shah Alam, 2009)
The overall aim of this paper is to evaluate the impact of new information and communication technologies (ICTs), in particular the digital convergence, upon new mode of governance in Malaysia. The researcher questions whether changes adopted by the Malaysian Government will be sufficient to meet the implicit objective of developing a new mode of governance that is at the core of the country's information age agenda. More specifically, this paper addresses two research questions. First, how and why the `old regime' of governance is affected by digital convergence in Malaysia and, second, whether Malaysia is capable of embracing the opportunities brought by digital convergence and effectively addressing the challenges through institutional and regulatory reforms. The study is rooted within the larger debate of the policy network with an attempt to generate further analysis of new mode of governance impacted by ICT in the context of Malaysia. The main sources of data and methodologies used in this paper include, content analysis of Malaysian government policy documents and Parliamentary hansards and semi-structured interviews with key policy makers, regulators, and experts of Malaysian ICT and convergence initiatives.